Neonatal Nonketotic Hyperglycinemia: Report of Two Cases - Yalçın Çelik; Selvi Gülaşı; Aytuğ Atıcı; Mustafa Kömür; Ali Haydar Turhan; Ergül Bolat (Güncel Pediatri)
Introduction: Nonketotic hyperglycinemia is an autosomal recessive disorder of glycine metabolism caused by a defect in the the glycine cleavage system. Case 1: A 3-day-old female baby was admitted to emergency room of a public hospital due to cyanosis and was hospitalized after resuscitation. She was transferred to our hospital on the seventh day of mechanical ventilation. Her delivery was uneventful but she refused feeding after birth. Her parents were consanguineous with a fourth degree of relationship. She was hypotonic and lethargic and had unresponsive neonatal reflexes. She had persistent hiccups and myoclonic convulsions. Complete blood count, biochemical parameters, tandem mass and urinary organic acid analysis were within normal limits. Cranial magnetic resonance imaging showed a thin corpus callosum. Electroencephalographic monitoring revealed burst suppression pattern. The CSF- to-plasma glycine concentration ratio was 0.32. According to these findings, our patient was diagnosed as neonatal nonketotic hyperglycinemia and was treated with dextromethorphan and sodium benzoate. Case 2: A male baby, born at a public hospital, was admitted to newborn intensive care unit due to poor feeding and cyanosis. On the second day of life, myoclonic convulsions were observed and he was transferred to our hospital. Her parents were consanguineous with a third degree of relationship. He was hypotonic and lethargic and had unresponsive neonatal reflexes. Complete blood count, biochemical parameters, tandem mass and urinary organic acid analysis were within normal limits. Cranial magnetic resonance imaging showed a thin corpus callosum. Cranial magnetic resonance spectroscopy revealed an elevated glycine peak at 3.56 ppm. The CSF- to-plasma glycine concentration ratio was 0.21. According to these findings, our patient was diagnosed as neonatal nonketotic hyperglycinemia and was treated with dextromethorphan and sodium benzoate. Conclusion: Nonketotic hyperglycinemia should be considered in newborns with unidentified hypotonia, convulsions, lethargy and coma. (Journal of Current Pediatrics 2011; 9: 137-40)